KAJIAN NORMATIF TENTANG PROSES PELAKSANAAN PEMBEBANAN JAMINAN FIDUSIA ATAS JAMINAN PERSEDIAAN BARANG DAN PIUTANG DAGANG DI DUNIA PERBANKAN - Rizayusmanda, Rizayusmanda (Faculty of Law, University of Palembang, 2019)
Banking is an institution that is vulnerable to risks related to money. The banking position as a mediator that connects those with surplus and financial deficits, banks must maintain good relations with the two parties. Banking decisions must be moderate, namely considering the desires of both parties because without the two parties, banking activities are not running. But if you are not careful in disbursing loans, bad credit will occur, then to protect the money disbursed, the debtor must provide collateral to the bank. This paper is a normative legal research that is research aimed at written regulations relating to the procedure for carrying out fiduciary collateral for collateral in the form of inventory and trade receivables according to Fiduciary Law Number 42 of 1999, and the legal consequences if the collateral is in the form of inventory the goods and receivables are not processed by loading fiduciary and registering them to the Fiduciary Registration Office. In the implementation of Fiduciary Collateral Imposition, especially collateral for credit in the form of goods and trade receivables, as determined by law, by registering the Fiduciary Deed of Registration with the Fiduciary Registration Office - Ministry of Law and Human Rights. For collateral for loans financed by banks, the Actions made under the hand or Notarial but not registered with the Fiduciary Deed of Registration at the Fiduciary Security Registration Office, do not get preferential rights and an executorial right guaranteed by the Fiduciary Guarantee Institute, and the Fiduciary Guarantee Agreement is only in the form of a Fiduciary Deed Registration Office. under the hand that has no executive power